Utilization of Drones for Infrastrucure Mapping in Kamisi Village, Kodeoha District, North Kolaka Regency - Prasetya, Arif; Hasidu, La Ode Abdul Fajar; Fitra, Ramad Arya (Majalah Pengabdian Indonesia, 2025)
This community service activity aims to map the infrastructure and boundaries of Kamisi Village, Kodeoha District, North Kolaka Regency used drone. Mapping is carried out as an effort to support the implementation of planned and sustainable village development. This activity was carried out for two months (February-April) in 2023. The implementation method consists of 5 stages: 1) location survey, 2) taking coordinate points using GPS, 3) taking aerial photos using the DJI Mavic2 Pro Drone which supports mapping activities, 4) data processing with Arc.GIS software, and 5) submission of maps to the village government. The results obtained are detailed maps of infrastructure (village gates, village offices, roads and bridges), hamlet boundaries, residential areas, plantation/agricultural areas, and village public facilities (sports fields, places of worship/mosques, health facilities such as integrated health posts and health centers, and TPU). This map is expected to be a reference for village development and minimize the potential for conflict between villages and hamlets regarding territorial boundaries. Active participation of the community and village government shows high support for synergy between universities and villages in regional development.